Productivity and the Euro Dollar exchange rate puzzle - Alquist, Ron; Chinn, Menzie David (NBER working paper series, 2002)
This paper documents the evidence for a productivity based model of the dollar/euro real exchange rate over the 1985-2001 period. We estimate cointegrating relationships between the real exchange rate, productivity, and the real price of oil using the Johansen (1988) and Stock-Watson (1993) procedures. We find that each percentage point in the US-Euro area productivity differential results in a five percentage point real appreciation of the dollar. This finding is robust to the estimation methodology, the variables included in the regression, and the sample period. We conjecture that productivity-based models cannot explain the observed patterns with the standard set of assumptions, and describe a case in which the model can be reconciled with the observed data.